Patrimônio Universitário da UFMG: construção de um panorama de seus imóveis protegidos - Daniele Rodrigues Serra Lopes (2022)
Throughout the 20th and 21st centuries, the expansion of the concepts surrounding the heritage allowed new elements to receive recognition and protection from the public power through initiatives, such as the creation of legal norms for preservation and administrative actions such as tipping. One of the groups to benefit from this expansion are the movable and real estate managed by universities, this set can be defined as "University Heritage". In Brazil, a significant portion of the listed assets is under the responsibility of universities, focusing more significantly on public universities. The way in which each institution deals with listed properties is diverse, and most universities do not have information about their protected assets, in a systematized, clear and available to the population. In some cases, it is identified that the institution itself does not know the whole for which it is responsible. The Federal University of Minas Gerais is one of the examples where the narrative about University Heritage is deficient. For this reason, it is proposed the mapping and registration of its listed properties or in the process of tipping in order to subsidize integrated management policies of this property that can ensure better conditions for the properties in question. A methodology was developed for structuring the main information of each good, based on the work developed by the University of São Paulo, in which through indirect documentation (documentary and bibliographic research) and direct documentation (field research) a database was created. The same system was applied to UFMG properties that are protected. The consolidation of information was divided into a higher level of detail for the goods located in Belo Horizonte and a lower level for the other goods. The result achieved is unprecedented for the institution and seeks to be a subsidy for discussions about this group.